2001
DOI: 10.1007/s004390000422
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of the MECP2 gene: prevalence of recurrent mutations and gross DNA rearrangements in Rett syndrome patients

Abstract: Mutations in the X-linked methyl-CpG-binding protein 2 gene (MECP2) have been found to be a cause of Rett syndrome (RTT). In order to provide further insights into the distribution and the spectrum of mutations, we investigated, in addition to the whole coding sequence, a phylogenetically conserved sequence within the 3' untranslated region (3' UTR) of the MECP2 gene for 55 sporadic RTT, including 47 typical and 8 nonclassical cases. We have developed an approach based on conformation-sensitive gel electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 21 publications
7
54
1
3
Order By: Relevance
“…Mutations were identified in nine of 13 cases (Table I), yielding a mutation rate of 69%, which is consistent with previous reports [De Bona et al, 2000;Auranen et al, 2001;Bourdon et al, 2001;Laccone et al, 2001;Nicolao et al, 2001;Vacca et al, 2001]. Eight of the nine mutations (89%) were C to T transitions at CpG dinucleotides.…”
Section: Resultssupporting
confidence: 85%
“…Mutations were identified in nine of 13 cases (Table I), yielding a mutation rate of 69%, which is consistent with previous reports [De Bona et al, 2000;Auranen et al, 2001;Bourdon et al, 2001;Laccone et al, 2001;Nicolao et al, 2001;Vacca et al, 2001]. Eight of the nine mutations (89%) were C to T transitions at CpG dinucleotides.…”
Section: Resultssupporting
confidence: 85%
“…This variant in the 3'UTR has been reported previously. 4 In patient 18, a C?G transversion at nucleotide 1141 leads to a novel Proline to Alanine substitution at residue 381 (P381A). Familial analysis in this case indicated that this P381A allele is a benign polymorphism, because the unaffected father carried the same variant.…”
Section: Resultsmentioning
confidence: 99%
“…Again, some of the individuals had more than one sequence change, indicating that there is a high variability in the 3 0 UTR. All of the variations encountered were novel, except the c.9964insC [Bourdon et al, 2001]. Ten of the changes were common to both patients and controls, suggesting that they do not have any pathogenic effect.…”
Section: Variation Of the Mecp2 Coding Region And Exon-intron Boundarmentioning
confidence: 89%